1998
DOI: 10.1161/01.str.29.12.2556
|View full text |Cite
|
Sign up to set email alerts
|

99m Technetium-Ethyl-Cysteinate-Dimer Single-Photon Emission CT Can Predict Fatal Ischemic Brain Edema

Abstract: Background and Purpose-We sought to study the prognostic value of early 99m technetium-ethyl-cysteinate-dimer single-photon emission CT (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 57 publications
4
42
1
1
Order By: Relevance
“…29 Studies using 99m Tc-ethyl-cysteinatedimer perfusion single photon emission CT have shown that complete middle cerebral artery territory activity defect is an independent predictor of MMI. 30 Two MRI studies have looked at MMI. In one study, 31 DWI was performed within 14 hours in 28 patients with proven middle cerebral artery or carotid T occlusion.…”
Section: Malignant MMImentioning
confidence: 99%
“…29 Studies using 99m Tc-ethyl-cysteinatedimer perfusion single photon emission CT have shown that complete middle cerebral artery territory activity defect is an independent predictor of MMI. 30 Two MRI studies have looked at MMI. In one study, 31 DWI was performed within 14 hours in 28 patients with proven middle cerebral artery or carotid T occlusion.…”
Section: Malignant MMImentioning
confidence: 99%
“…[3][4][5] However, the critical questions regarding DHC remain: whom to treat and when to treat. Attempts to establish reliable diagnostic tools to identify patients at particular risk of malignant MCA infarction have included determinations of diffusion-and perfusion-weighted MRI parameters, 6,7 of a critical lesion volume on computed tomography (CT), 8,9 of cerebral blood flow by means of single-photon emission CT, 10 or of metabolic measures using positron emission tomography (PET) and microdialysis. 11 Clearly, most of these procedures are relatively time consuming and not always feasible.…”
mentioning
confidence: 99%
“…Other small studies have supported the prognostic role of major CT findings and other neuroimaging data but failed to identify any clinical or laboratory predictors of outcome. 14,15 Therefore, we evaluated the early clinical, laboratory, and radiographic characteristics associated with fatal brain edema after stroke in a larger, broad-based patient population.…”
mentioning
confidence: 99%